2013
DOI: 10.1371/journal.pone.0065398
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Duration among Children 8 Months after the 2011 Japan Earthquake and Tsunami

Abstract: BackgroundTo elucidate relationships between disaster damage conditions and sleep duration among children who survived the 2011 Japan earthquake and tsunami.MethodsThe subjects comprised 12,524 children in kindergartens, elementary schools, and junior high schools in Ishinomaki City, Miyagi Prefecture, Japan. The Post Traumatic Stress Symptoms for Children 15 items (PTSSC-15), a self-completion questionnaire on traumatic symptoms, and a sleep questionnaire were distributed to them. A questionnaire regarding di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 17 publications
1
29
0
Order By: Relevance
“…Our results are in line with prior research, which although limited, has found that children and adolescents exposed to disasters commonly have persistent sleep disturbances post-event, both when children and parents report symptomology (Brown, Mellman, Alfano, & Weems, 2011; Dirkzwager, Kerssens, & Yzermans, 2006; Geng, Fan, Mo, Simandl, & Liu, 2013; Usami et al, 2013). To the best of our knowledge, this is the first prospective study assessing sleep disturbances among children following natural disasters.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in line with prior research, which although limited, has found that children and adolescents exposed to disasters commonly have persistent sleep disturbances post-event, both when children and parents report symptomology (Brown, Mellman, Alfano, & Weems, 2011; Dirkzwager, Kerssens, & Yzermans, 2006; Geng, Fan, Mo, Simandl, & Liu, 2013; Usami et al, 2013). To the best of our knowledge, this is the first prospective study assessing sleep disturbances among children following natural disasters.…”
Section: Discussionsupporting
confidence: 92%
“…Previous findings have indicated an association between PTSD and other psychological symptoms such as anxiety and depression (Fan et al, 2011; Goenjian et al, 2011; Lai et al, 2015, 2013), higher risks of behavioural problems, substance abuse and sleep disturbance (Pfefferbaum et al, 2015; Usami et al, 2013). This further highlights the importance of studying more diverse symptoms, particularly psychosomatic symptoms.…”
Section: Discussionmentioning
confidence: 96%
“…We have conducted a large‐scale screening for symptoms of psychiatric illness using the PTSSC‐15. We now demonstrate that, in addition to signs of post‐traumatic stress, these children exhibit sleep disturbances that may exacerbate pre‐existing symptoms or trigger delayed depression, anxiety, and PTSD.…”
Section: Discussionmentioning
confidence: 77%
“…In addition to PTSD, the risks of depression and anxiety disorders also increase after a disaster . We previously reported the results of an investigation on traumatic symptoms in children conducted approximately 8 months after the 2011 earthquake and tsunami . However, the self‐completion questionnaire used, the Post Traumatic Stress Symptoms for Children‐15 items (PTSSC‐15), contains only one item on sleep disruption.…”
Section: Introductionmentioning
confidence: 99%
“…The long-range electrostatic forces were evaluated using the classical particle mesh Ewald (PME) method [56] while chemical bonds between hydrogen and heavy atoms were constrained to their equilibrium value. To describe the interactions, the Charmm36 [57,58] force field was used.…”
Section: Computational Method: Preparation Of Models For Minimizationmentioning
confidence: 99%